2012
DOI: 10.1155/2012/851276
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Anxiety Symptoms Relate to Distinct Components of Pain Experience among Patients with Breast Cancer

Abstract: Breast cancer is a leading cancer diagnosis among women worldwide, with more than 210,000 new cases and 40,000 deaths per year in the United States. Pain, anxiety, and depression can be significant factors during the course of breast cancer. Pain is a complex experience with sensory, affective, and cognitive dimensions. While depression and anxiety symptoms are relatively common among breast cancer patients, little is known about the relation between these psychiatric factors and distinct components of the pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 17 publications
1
26
2
3
Order By: Relevance
“…Predictors of anxiety on cancer patients were severe pain (Galloway et al, 2012), functional limitations (Khan, Amatya, Pallant, & Rajapaska, 2012), and history of traumatic experiences (Green et al, 2000). Recently, Ploos van Amstel et al (2013) determined that more than one third of breast cancer survivors experienced emotional distress (anxiety, depression, etc.…”
Section: Anxietymentioning
confidence: 99%
“…Predictors of anxiety on cancer patients were severe pain (Galloway et al, 2012), functional limitations (Khan, Amatya, Pallant, & Rajapaska, 2012), and history of traumatic experiences (Green et al, 2000). Recently, Ploos van Amstel et al (2013) determined that more than one third of breast cancer survivors experienced emotional distress (anxiety, depression, etc.…”
Section: Anxietymentioning
confidence: 99%
“…However, Tavoli et al [3] reported differences in the patients who experienced pain for a long time and prolonged disease duration. A study by Galloway et al [23] that enrolled women with breast cancer also supported a correlation between the duration of pain and anxiety or depression. The authors did not find a relation between the severity of pain and anxiety or depression at 3-months follow-up, whereas they did find that pain was related to both anxiety and depression at an18-months follow-up.…”
Section: Discussionmentioning
confidence: 82%
“…Recent studies have reported that pain and the severity of pain were significantly associated with depressive and anxiety symptoms. [2,[23][24][25][26][27] It has been suggested that anxiety and depression independently contributed to the emergence of mental health and somatic symptoms, [27] pain-aggravated mood disorders. [25] Thus, a significant correlation between physical symptoms, such as pain, and depression and/or anxiety might be more common in depressed cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly associated psychological comorbidities in pain are depression and anxiety 178180. These may be preexisting or may result from the pain itself, often aggravated in untreated or undertreated chronic pain 181. Presence of depression is known to have considerable impact on outcomes of pain treatment, signifying the two-way relationship between pain and depression.…”
Section: Management Mythsmentioning
confidence: 99%